Direct renin inhibition in chronic kidney disease - Persson, Frederik (Blackwell Science Inc, 2013)
For approximately 6 years, the only commercially available direct renin inhibitor, aliskiren, which inhibits the renin-angiotensin-aldosterone system at the initial rate limiting step, has been marketed for the treatment of hypertension. Concurrently, much attention has been given to the possibility that renin inhibition could hold potential for improved treatment in patients with chronic kidney disease, with diabetic nephropathy as an obvious group of patients to investigate, as the activity of the renin-angiotensin-aldosterone system is enhanced in these patients and as there is an unmet need for improved treatment and prognosis in these patients. Several short term studies have been performed in diabetic nephropathy, showing a consistent effect on the surrogate endpoint lowering of albuminuria, both as monotherapy and in combination with other blockers of the renin-angiotensin-aldosterone system. In addition, combination treatment also seemed safe and effective in patients with impaired kidney function. These initial findings formed the basis for the design of a large morbidity and mortality trial investigating aliskiren as add-on to standard treatment. The study has just concluded, but was terminated early as a beneficial effect was unlikely and there was an increased frequency of side effects. Also in non-diabetic kidney disease a few intervention studies have been carried out, but there is no ongoing hard outcome study. In this review we provide the current evidence for renin inhibition in chronic kidney disease by reporting the studies published so far as well as a perspective on the future possibilites.